(untitled) (Indian Journal of Child Health, 2020)
Introduction: Worldwide, sickle cell disease (SCD) is the most common hemoglobinopathy among which SS pattern is more common. Although hydroxyurea (HU) is approved by the Food and Drug Administration for the treatment of recurrent moderate-to-severe painful crises in pediatric sickle cell anemia, there is a fear of toxicities. Objectives: The objectives of the study were to evaluate the short-term safety and beneficial effects of low-dose HU therapy in SCD (SS pattern) children. Materials and Methods: This prospective cohort study enrolled 40 cases of severe SCD and started HU in a fixed dose of 10 mg/kg/day. During follow-up, cases were evaluated for compliance of HU, its toxic effects and adverse events from their histories, clinical examinations, and laboratory parameters. Furthermore, beneficial effects of HU therapy were evaluated by assessing blood transfusion rate, frequency of painful events, strokes, acute chest syndrome, avascular necrosis of femur, and estimation of hemoglobin F (HbF) level after 2 years of therapy. HU was discontinued temporarily if any toxicity or minor adverse drug events occurred during therapy and was restarted at the same dose after normalization of deranged laboratory parameters. Results: The clinical adverse drug events seen were nausea (8.33%), diarrhea (2.78%), and hematuria (2.78%). The most common hematological toxicity was anemia and thrombocytopenia. Renal and hepatic toxicities were transient in nature. The mean acute painful events and blood transfusion rate reduced significantly on HU therapy. It increased Hb and HbF level significantly in SCD children. Conclusion: HU is a safe drug without significant toxicity or adverse events in a dose of 10 mg/kg/day for short duration and it is beneficial in SCD (SS pattern) children in reducing acute painful events and decrease blood transfusion rate.